The WTO's international multilateral trade system and its effects on the production and consumption of food - Barbosa Junior, Ricardo Cesar; Coca, Estevan [UNESP] (Inst Brasileiro Relacoes Int, 2015)
Upon the WTO's 20th anniversary this paper evaluates how its free trade regime has impacted the way people grow and eat food. Further on, we describe how food sovereignty emerged as a counter proposal that aims to once again make food about people and not profit.
Keywords: World Trade Organization; International Food Trade; Food Sovereignty